Peningkatan Kesehatan melalui Penapisan Kadar Hemoglobin dan Hematokrit di Yayasan Baptis Cengkareng - Wijaya, Christian; Santoso, Alexander Halim; Destra, Edwin; Soebrata, Linginda; Setia, Nicholas; Pratama, Aditya (PPNI UNIMMAN, 2025)
Hemoglobin and hematocrit levels are fundamental hematological screening parameters that are relevant for identifying potential erythropoiesis disorders. An imbalance in these two parameters often reflects undiagnosed anemia, especially in adults and the elderly. The activity was carried out at the Cengkareng Baptist Foundation using the Plan–Do–Check–Act (PDCA) approach. The examination was carried out using the capillary method based on Point-of-Care Testing (POCT). Nutrition education was provided using leaflets containing information about the importance of micronutrients for blood formation. A total of 62 participants took part in this activity, with an age range of 23–76 years. Most participants were female (74.2%). Hemoglobin values ​​ranged from 7.4 to 17.3 g/dL, with a median of 11.9 g/dL. A total of 64.5% of participants had anemia. Hematocrit values ​​ranged from 22.0 to 51.0%, with a median of 35.0%. The high prevalence of anemia identified through this screening underscores the importance of preventive efforts through targeted nutritional education. Emphasis should be placed on the adequate intake of iron, vitamin B12, and folate to promote behavior change and reduce anemia risk in the community.